Surgical Management of Lumbar Adhesive Arachnoiditis Postmeningitis: A Bermuda Triangle?—Case Report and Review of Literature - Vadlamani, Tejaswi; Yagnick, Nishant S.; Kagita, Rakesh; Sinha, Sumit (Indian Journal of Neurosurgery, 2023)
Spinal arachnoiditis can occur as a delayed sequel of meningitis. Cerebrospinal fluid flow disturbances and adhesive loculations can cause cord compression and traction on roots causing the symptoms. The surgical treatment of this condition is often considered a limited option, because of the high chances of recurrence of symptoms and adhesions, often considered as surgical failure. Here, we report a patient with extensive lumbar–sacral adhesive arachnoiditis successfully treated with limited adhesiolysis under neuromonitoring and cystoperitoneal shunt placement.
Keywords: spinal adhesive arachnoiditis; adhesiolysis; cystoperitoneal shunt; neuromonitoring